Oxochlorides of Rhenium - Frais, Wolfgang Peter (My University, 1972)
The reaction of rhenium pentachloride and rhenium trioxide in the presence and absence of traces of water was investigated with the intent of identifying, isolating and characterizing new oxochlorides of rhenium. Depending on the conditions of reaction, various amounts of ReCl₅, ReO₃, Re₃Cl₉, ReO₂, rhenium metal, ReO₃Cl, ReOCl₄, ReOCl₄.ReO₃Cl, ReOCl₄(OH₂), Re₂O₃Cl₆(ReO₃Cl)₂ and ReOCl₂ were identified among the products. The compounds ReOCl₄(OH₂), ReOCl₂ and Re₂O₃Cl₆(ReO₃Cl)₂ had not been reported previously. They were characterized by a combination of single crystal X-ray diffraction, X-ray powder photography, neutron activation analysis, infrared and Raman spectroscopy and observation of physical and chemical properties. In addition, improved methods of preparation were found.
ReOCl₄(OH₂) consists of molecules of pseudo-octahedrally coordinated rhenium(VI), with the aquo-group (Re-Aq = 2.27(2) Å) trans to the terminal oxo-group (Re=O = 1.63(2) Å). The average Re-Cl bond length is 2.29(1) Å.
The molecules of Re₂O₃Cl₆(ReO₃Cl)₂ are composed of a dimeric Re₂O₃Cl₆ unit with a bridging oxygen atom at the center of symmetry and an Re-O (bridge) distance of 1.847(1) Å. The remaining oxo-group on each rhenium atom is cis to the bridge and is strongly bonded (1.69(2) Å), and the position trans to the terminal oxo-group is filled by a weak bond (2.41(1)Å) to an oxygen atom of a perrhenyl chloride molecule.
The structure of ReOCl₂ could not be solved by single crystal X-ray techniques because of an apparent disorder in the structure, but characterization of this compound was achieved by a combination of analyses and the observed stoichiometry of the reactions
[equations removed]
Although ReOCl₂ is much more reactive than MoOCl₂ and WOCl₂, the physical and chemical properties of these compounds are somewhat similar.
The chemistry of the rhenium-oxygen-chlorine system is discussed and compared to that of technetium, molybdenum and tungsten.
Keywords: Chemistry; Chemistry